(untitled) (Bangladesh Journal of Microbiology, 2016)
Vibrio parahaemolyticus is a halophilic bacterium and lives in coastal water and causes gastroenteritis in humans especially where the rate of seafood consumption is high. Although it is a marine organism, very less is known about its pandemic spreading in the fresh water environment across Bangladesh. The present study was, therefore, undertaken to isolate and investigate the virulence potential, as well as phenotypic and genotypic traits of V. parahaemolyticus strains occurring in the fresh water environments around coastal southern parts of Bangladesh. A total of 70 suspected colonies of V. parahaemolyticus were isolated from water, sediment and roots of water hyacinth samples collected from four different locations of Bishkhali river located in Barisal district of Bangladesh. Of the 70 colonies, fourteen isolates were confirmed as V. parahaemolyticus. PCR detection for the presence of toxR, trh and tdh genes among these seven isolates using primers specific for toxR, trh and tdh revealed that all seven were positive for toxR but negative for trh or tdh genes. The results indicate that the isolates under this study do not contain virulence properties that correlate to the ability of causing infection and diseases. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 61-64